Enhanced well-being in second language learners: unraveling the roles of emotion regulation and resilience - Shi, Hong; Gao, Jiayao (Frontiers in Psychology, 2025)
With the growing interest in positive psychology, the roles of well-being, emotion regulation, and resilience in second language acquisition (SLA) have attracted increasing attention. Emotion regulation aids in maintaining positive emotions and managing study stress, while resilience helps individuals maintain a positive attitude and recover swiftly from difficulties. Both factors significantly impact the well-being of SLA learners. This study investigated the relationship among these variables using questionnaires on 157 English language learners from a top university in China. Correlation and regression analyses, conducted using SPSS, revealed significant positive correlations between emotion regulation (cognitive reappraisal and expressive suppression), resilience, and well-being. Resilience exhibited the strongest correlation with well-being, followed by its correlation with cognitive reappraisal and expressive suppression. Cognitive reappraisal had a significant positive predictive effect on well-being, with resilience partially mediating this relationship. On the other hand, expressive suppression indirectly affected well-being solely through resilience. The findings underscore the importance of enhancing emotion regulation skills and resilience to improve SLA learners’ well-being, providing insights for educational strategy development and learner support.